The diversity, distribution, biomass, and conservation status of ichthyofauna of the Singkil peat swamp in Aceh Province, Indonesia - NANDA MUHAMMAD RAZI; MUHAMMAD NASIR; KHALIDIN KHALIDIN; DEA SAVIRA; ISTAFAN NAJMI; MAHFUD MAHFUD; FEBRI DERMAWAN; NUR FADLI; ZAINAL A. MUCHLISIN (Society for Indonesian Biodiversity, 2023)
Abstract. Razi NM, Nasir M, Khalidin K, Savira D, Najmi I, Mahfud M, Dermawan F, Fadli N, Muchlisin ZA. 2023. The diversity, distribution, biomass, and conservation status of ichthyofauna of the Singkil peat swamp in Aceh Province, Indonesia. Biodiversitas 24: 6661-6674. The land conversion of the Singkil peat swamp into oil palm plantations poses a significant threat to the aquatic ecosystem, with potentially detrimental consequences for fish biodiversity. Several reports showed that there was no data on fish diversity in the Singkil peat swamp despite the damage occurring in the area. Therefore, this study aimed to analyze the diversity, distribution, biomass, and conservation status of Ichthyofauna in the Singkil peat swamp waters. Sampling was carried out at 13 locations from July 2023 to August 2023, and the samples were caught using gill nets, casting nets, fishing rods, and traps. A total of 934 samples were collected during the sampling, belonging to 39 species, 31 genera, and 26 families. The results showed that Cyprinidae was the most dominant family, with an average diversity index of 1.23, indicating the medium category. The average dominance index was 0.42, which was placed in the low category. Channa striata (Bloch, 1793) and Trichopodus trichopterus (Pallas, 1770) had the highest frequency of occurrence and were found in seven locations out of 13 surveyed. Furthermore, these species were categorized as frequently found based on their availability. The average fish biomass was 288.75 kg/ha, with C. striata having the largest value. Among the 39 fish species obtained, 3 species were classified as near threatened, including Anguilla bicolor (McClelland, 1844), Mystus bimaculatus (Volz, 1904), and Kryptopterus minor (Roberts, 1989), while 1 invasive sample was recorded, namely Oreochromis niloticus (Linnaeus, 1758) in one location.